The phenomenon of re-performance in dedicatory epigrams and Pindar’s Odes (Circe de clásicos y modernos, 2018)
In this article I will analyze the relation be-tween dedicatory epigrams and Pindaric Odes, paying special attention to the possibilities of re-performance that both genres present. In this sense, the repetition of epigrams as well as that of Epinikia allows to actualize the athlete ́s triumphs and his consequent glory and to renew the bond with the divinity under whose auspice the victory took place. In order to exemplify this phenomenon I will conduct a study of Olympian 7 and of a selected corpus of dedicatory epigrams.
Keywords: Pindar; epigram; Epinikion; re-performance; divinity